Position Of The Supreme Court Decision Number 23 P/HUM/2024 After The Constitutional Court Decision Number 70/PUU-XXII/2024 - Oktafiani Zendrato; Ardilafiza (UNIB Press, 2025)
Supreme Court Decision Number 23 P/HUM/2024 and Constitutional Court Decision Number 70/PUU-XXII/2024 are two decisions related to the age requirements for regional head candidates which were initially followed up by the House of Representatives and ultimately the House of Representatives chose to follow Constitutional Court Decision Number 70/PUU XXII/2024. The purpose of this research is to find out how the authority of the Supreme Court and the Constitutional Court in testing laws and regulations related to the Regional Elections and what is the position of the Supreme Court Decision Number 23 P/HUM/2024 after the Constitutional Court Decision Number 70/PUU-XXII/2024. This research method is a normative legal research using a statutory approach and a conceptual approach. The results of the study show that the authority of the Supreme Court and the Constitutional Court in testing statutory regulations related to regional head elections has different scopes of authority. The Supreme Court has limited authority to test statutory regulations under the law against the law, one of which is the General Election Commission Regulation as a derivative regulation of the Regional Head Election Law and does not have the authority to test the Regional Head Election Law, while the Constitutional Court has the authority to test laws against the 1945 Constitution of the Republic of Indonesia, one of which is in testing the Regional Head Election Law. Meanwhile, Supreme Court Decision Number 23 P/HUM/2024 regarding the testing of age requirements for regional head candidates has a lower position when it is used as a basis for the formation of laws and regulations and when used as jurisprudence. Therefore, as a practical contribution, the Supreme Court and the Supreme Court should strengthen their understanding of the limits of authority possessed in testing laws and regulations. Although the authority of the Supreme Court and the Constitutional Court is different, coordination between these two institutions is still necessary to create consistency in the application of the law. Therefore, there needs to be a more intensive dialogue between these institutions related to intersecting issues, such as testing laws and regulations related to the Regional Elections.